Designing a Metacognition–Social Complexity-Based Model for Science Subject in Elementary Education: A Comprehensive Needs Analysis Study - Prafitasari, Ferrinda; Haryanto; Hastuti, Woro Sri (International Electronic Journal of Elementary Education, 2025)
Enhancing Higher Order Thinking Skills (HOTS) and collaborative abilities is a strategic necessity in elementary science education, aligning with the requirements of 21st-century competences. Previous research have demonstrated the shortcomings of traditional methods that fail to incorporate metacognitive and social complexity elements, along with the absence of a mixed-method requirements analysis. This study seeks to ascertain the foundational conditions of Higher Order Thinking Skills (HOTS) and collaborative abilities, investigate the perceptions of educators and learners concerning developmental obstacles and possibilities, delineate the requirements of a MetaSC-based learning model, and identify critical components pertinent to the elementary school environment. The exploratory sequential mixed-method approach involved conducting in-depth interviews during the qualitative phase and utilizing a questionnaire in the quantitative phase. The findings indicated that students' higher-order thinking skills (HOTS) were rated as low (mean = 2.49), particularly in creative talents, although collaborative skills fell into the intermediate range (mean = 3.11), exhibiting deficiencies in communication. The primary impediments consist of inadequate infrastructure, restricted learning time, and the prevalence of lecture-based methodologies. The findings necessitate the development of a Metacognition–Social Complexity (MetaSC) model that integrates project-based techniques, technological incorporation, and educator training to enhance creativity and communication. This study theoretically enhances the literature on the integration of metacognition and social complexity, while realistically offering ideas for developing learning models that address the actual needs of educators and learners.